2023
DOI: 10.1093/toxsci/kfad031
|View full text |Cite
|
Sign up to set email alerts
|

Triazole fungicides induce adipogenesis and repress osteoblastogenesis in zebrafish

Abstract: Triazoles are a major group of azole fungicides commonly used in agriculture, veterinary, and human medicine. Maternal exposure to certain triazole anti-fungal medication causes congenital malformations, including skeletal malformations. We hypothesized that triazoles used as pesticides in agriculture also pose a risk of causing skeletal malformations in developing embryos. In this study, teratogenic effects of three commonly used triazoles, cyproconazole, paclobutrazol, and triadimenol, were investigated in z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Agonists for the Vdr (calcitriol) or Rar (retinoic acid) were used as reference compounds and their chemical similarities were computed to all compounds in the POP mix. In addition, 4 triazole fungicides with a potential to be endocrine disruptors and posing serious concerns were chosen to complete the analysis: flusilazole, triadimenol, diniconazole and hexaconazole [52][53][54][55][56][57][58][59]. Hierarchical agglomerative nesting clustering was performed using the chemical fingerprints (toxprints) of all these compounds (Fig 7).…”
Section: Chemical Similarities Between Pops and Retinoids Or Vitamin Dmentioning
confidence: 99%
“…Agonists for the Vdr (calcitriol) or Rar (retinoic acid) were used as reference compounds and their chemical similarities were computed to all compounds in the POP mix. In addition, 4 triazole fungicides with a potential to be endocrine disruptors and posing serious concerns were chosen to complete the analysis: flusilazole, triadimenol, diniconazole and hexaconazole [52][53][54][55][56][57][58][59]. Hierarchical agglomerative nesting clustering was performed using the chemical fingerprints (toxprints) of all these compounds (Fig 7).…”
Section: Chemical Similarities Between Pops and Retinoids Or Vitamin Dmentioning
confidence: 99%
“…The widespread use of triazoles has allowed their accumulation in the environment in substantial amounts, and they are causing adverse effects in non-target organisms, posing a great risk to environmental and human health [ 7 ]. It has been experimentally demonstrated that triazoles can reduce skeletal formation in developing zebrafish, promoting bone malformations [ 8 ]. In mammals, in an ex vivo study it was observed that the murine heart is sensitive to the triazole tebuconazole, which was able to induce cardiac arrhythmia and cardiac electrical remodeling by blocking calcium and potassium currents; both effects produced by tebuconazole represent a potential risk to mammalian cardiac function [ 9 ].…”
Section: Introductionmentioning
confidence: 99%